M2-AChR Mediates Rapid Antidepressant Effects of Scopolamine Through Activating the mTORC1-BDNF Signaling Pathway in the Medial Prefrontal Cortex - Liu, Shuang; Shi, Dandan; Sun, Zuoli; He, Yi; Yang, Jian; Wang, Gang (Frontiers in Psychiatry, 2021)
Background: Scopolamine, a non-selective muscarinic acetylcholine receptor (M1 5-AChR) antagonist, has rapid and robust antidepressant effects in humans and other species. However, which of the five M-AChRs mediates these therapeutic effects has not been fully identified. Several studies implicate M2-AChR as a potential antidepressant target of scopolamine. This study aimed to explore the role of M2-AChR in scopolamine's antidepressant-like effects and determine the underlying mechanisms. Methods: We used the classic novelty suppressed feeding test (NSFT), open field test (OFT) and forced swim test (FST) to observe antidepressant-related behaviors of normal rats, medial prefrontal cortex (mPFC) neuron silenced rats and M2-AChR knockdown rats treated with scopolamine. In a further experiment, the M2 cholinergic receptor antagonist methoctramine (MCT) was injected intracerebroventricularly into normal rats. Levels of mTORC1 and brain-derived neurotrophic factor (BDNF) in the mPFC of animals were analyzed by Western blotting. Results: Consistent with previous studies, mPFC was required for the antidepressant-like effects of scopolamine, and intracerebroventricular injection of MCT into rats could produce similar antidepressant-like effects. Use of AAV-shRNA to knock down M2-AChR in the mPFC resulted in the antidepressant-like effects of scopolamine being blunted. Furthermore, Western blotting demonstrated increased expression of mTORC1 signaling and BDNF in MCT-treated rats. Conclusion: Our results indicate that M2-AChR in the mPFC mediates the antidepressant-like effects of scopolamine by increasing the expression of BDNF and activating the mTORC1 signaling pathway.